Early Biochemical Predictors of Survival in Intermediate and High-Risk Prostate Cancer Treated with Radiation and Androgen Deprivation Therapy - Patel, Mira A. (Radiother Oncol, 2019)
BACKGROUND AND PURPOSE: To identify early biochemical predictors of survival in intermediate- and high-risk prostate cancer patients with a pre-treatment PSA <20ng/mL following definitive radiation therapy (RT) and androgen deprivation therapy (ADT). MATERIALS AND METHODS: A single-institution review of 2,566 intermediate and high-risk prostate cancer patients treated with definitive RT and neoadjuvant and concurrent ADT from 1990-2012 was performed. The first prostate-specific antigen (PSA) value within three months of ADT initiation (post-ADT PSA) and the first PSA within three months after RT completion (post-RT PSA) were recorded. 1,275 had baseline PSA <20ng/mL and either post-ADT or post-RT PSA available. Median follow-up was 7.6 years. The relationship between post-treatment PSA kinetics and biochemical relapse (BR), distant metastasis (DM), prostate cancer specific death (PCSD) and overall survival (OS) was modeled using Cox regression univariate and multivariate analysis (MVA). RESULTS: MVA demonstrated a strong association between a post-RT PSA ≥0.09ng/mL and a significantly higher risk of BR (HR: 1.93; 95%CI: 1.45-2.57; p<0.001), DM (HR:2.97; 95%CI: 2.01-4.39; p<0.001), PCSD (HR:2.99; 95%CI: 1.73-5.15; p<0.001) and OS (HR:1.49; 95%CI: 1.18-1.86; p<0.001). Post-RT PSA reduction of ≥95% relative to the baseline PSA was associated with a significantly lower risk of BR (MVA HR:0.58; 95%CI: 0.41-0.83; p=0.003) and DM (MVA HR:0.47; 95%CI: 0.30-0.76; p=0.002). CONCLUSION: A PSA value ≥0.09ng/mL early after RT completion is associated with significantly worse prognosis across all clinical outcomes, and an early PSA reduction of ≥95% is associated with reduced risk of BR and DM. These findings may identify patients who require early aggressive systemic management for higher-risk disease.